BUILDING A SUSTAINABLE FUTURE: EMBRACING CIRCULAR ECONOMY FOR ECONOMIC RESILIENCE - Kavya Gandikota, (International Journal of Advances in Business and Management Research (IJABMR), 2025)
The study discusses the role that CE plays in creating a better future. The main objective of this paper is to discuss how the circular economy (CE) has been applied to sustain natural resources, strengthen economies, and promote global resource efficiency by transitioning from traditional models to sustainable business models. As discussed in this paper, the issues and opportunities of circular economy (CE) applications in industries are presented based on a thorough literature review of peer-reviewed research articles, case studies, and institutional databases. The study emphasises the need to equitably share the planet's limited natural resources. It examines several implementation barriers to the circular economy (CE) and proposes innovative solutions for integrating CE concepts into business operations through creative approaches. The paper highlights the long-term benefits of CE, arguing that sustainable entrepreneurship, Eco innovation, and resource optimisation can drive global economies toward environmental conservation and financial sustainability. Furthermore, the study underscores the urgency of adopting concerted measures to ensure that future generations inherit balanced and sustainable ecosystems. Previous studies have shown that implementing sustainable structures adds value to products and minimizes waste generation, thereby contributing to economic stability. Such transformative changes will help secure a healthy and balanced ecosystem for future generations. The research is based on case studies and scholarly articles focusing on cooperative strategies among communities, businesses, and governments, reflecting the collaborative essence of CE implementation.